The Nurse Spiritual Care Therapeutics Scale and Patient Beliefs in Indonesia: A Developmental Psychometric Study - Usman, Suharno (Journal of religion and health, 2026)
Across the globe, spiritual care provided by nurses is recognised as an integral component of patient care. The decision to administer this scale test was driven by the observation that the instruments employed by nurses, which are designed to be more straightforward, accessible and culturally aligned with Indonesian contexts, were not adequately addressing spiritual needs. The present study sought to assess the reliability and validity of the Indonesian version of the Nurse Spiritual Care Therapeutics Scale (NSCTS-I). The study comprised 147 participants in a pilot test and 343 participants divided into two sub-samples. Sub-sample one was used for exploratory factor analysis (EFA; 189), and sub-sample two for confirmatory factor analysis (CFA; 154) of nurses working in four public hospitals who served in inpatient wards such as internal medicine wards, surgical wards, mother and child care wards, dedicated units for treating patients with COVD-19, or other treatment rooms. Construct validity was established using content validity indexing, EFA, goodness-of-fit model of a CFA which exhibited the highest comparative fit index (CFI .957), the lowest of root-mean-square-error of approximation (RMSEA .039), and standardised root-mean-square residual (SRMR .022). The analysis results indicate that the model is a well-fitted model with acceptable error margins. Correlational analysis with internal reliability of the NSCTS-I was further substantiated by a Cronbach's alpha of 0.963, thereby affirming its excellent reliability. The content validity indexing process indicated a scale CVI (S-CVI/Ave and I-CVI) of .97, an S-CVI/UA of .87, and an ICC of .927. The NSCTS-I has been developed as a tool to assess and evaluate the frequency with which Indonesian nurses provide spiritual care, with the objective of ensuring that patients' spiritual needs are met in the future.